Gene expression related to Steviol glycoside synthesis produced in Stevia rebaudiana (bert.) Shoot culture induced with high far-red LED light in TIS RITA® bioreactor system - Melviana, Agustine Christela; Esyanti, Rizkita Rachmi; Setyobudi, Roy Hendroko; Mel, Maizirwan; Adinurani, Praptiningsih Gamawati; Burlakovs, Juris (ResearchersLinks, Ltd., 2021)
Steviol glycosides contained in Stevia leaves have considerable potential uses for the natural sweetener industry due to it’s antidiabetic properties, hence a large number of plant source is required to supply the industry. To overcome the hindrances in the propagation of Stevia plants using in vivo methods, an alternative technique of propagation using in vitro methods is needed. The micropropagation method with the RITA® (Recipient for Automated Temporary Immersion System) is used in the production of a large amount of stevia biomass in approximately a short period. The forming of flowers is one of the limiting factors interfering with the metabolite production, as the content of steviol glycoside will decrease after plant flowering dramatically. This mechanism happened because steviol glycoside synthesis and flowering process share the same precursor. However, this interfering factor could be inhibited by using a high-red LED induction to delay the flowering stage, which may contribute to higher biomass and glycoside concentrations through greater system productivity. Hitherto, there was no significant study about the effect of far-red LED induction to improve the steviol glycoside content of Stevia plants, particularly at the molecular level. This research was therefore performed in the TIS RITA® bioreactor system to evaluate the effect of far-red LED induction towards biomass growth, multigene expression related to steviol glycosides, and its derivatives, and also the metabolites produced in S. rebaudiana plant. The result showed that the increment of biomass and gene expressions (ent-KO, ent-KS, ent-KAH13, UGT85C2, UGT74G1, and UGT76G1) in high far-red LED RITA® was higher compared with control RITA®. To conclude, the system with a far-red LED induction in TIS RITA® was proven to give a positive effect towards stevia shoots growth and greater metabolites production (stevioside and rebaudioside-A) up to 37.15% and 22.99%, respectively.